Territories of Poverty : Rethinking North and South - Crane, Emma Shaw; Roy, Ananya (Book collections on Project MUSE., 2015)
Territories of Poverty challenges the conventional North-South geographies through which poverty scholarship is organized. Staging theoretical interventions that traverse social histories of the American welfare state and critical ethnographies of international development regimes, these essays confront how poverty is constituted as a problem. In the process, the book analyzes bureaucracies of poverty, poor people's movements, and global networks of poverty expertise, as well as more intimate modes of poverty action such as volunteerism. From post-Katrina New Orleans to Korean church missions in Africa, this book is fundamentally concerned with how poverty is territorialized. In contrast to studies concerned with locations of poverty, Territories of Poverty engages with spatial technologies of power, be they community development and counterinsurgency during the American 1960s or the unceasing anticipation of war in Beirut. Within this territorial matrix, contributors uncover dissent, rupture, and mobilization. This book helps us understand the regulation of poverty- whether by globally circulating models of fast policy or vast webs of mobile money or philanthrocapitalist foundations-as multiple terrains of struggle for justice and social transformation. Contributors: Somaya Abdelgany, Vincanne Adams, Hiba Bou Akar, Teddy Cruz, Luis Flores, Alyosha Goldstein, Christina Gossmann, Akhil Gupta, Ju Hui Judy Han, Michael B. Katz, Erica Kohl-Arenas, Anh-Thi Le, Bill Maurer, Jamie Peck, Rebecca Peters, Ananya Roy, Stuart Schrader, Emma Shaw Crane, Nik Theodore, Stephanie Ullrich, Loïc Wacquant.